Tissue inhibitor of matrix metalloproteinase-1 polymorphism, plasma TIMP-1 levels, and antihypertensive therapy responsiveness in hypertensive disorders of pregnancy - Luizon, M. R.; Palei, A. C. T.; Sandrim, Valéria Cristina [UNESP]; Amaral, L. M.; Machado, J. S. R.; Lacchini, R.; Cavalli, R. C.; Duarte, G.; Tanus-Santos, J. E. (Nature Publishing Group, 2014)
Tissue inhibitor of metalloproteinase (TIMP)-1 is a major endogenous inhibitor of matrix metalloproteinase (MMP)-9, which may affect the responsiveness to therapy in hypertensive disorders of pregnancy. We examined whether TIMP-1 polymorphism (g.-9830T>G, rs2070584) modifies plasma MMP-9 and TIMP-1 levels and the response to antihypertensive therapy in 596 pregnant: 206 patients with preeclampsia (PE), 183 patients with gestational hypertension (GH) and 207 healthy pregnant controls. We also studied the TIMP-3 polymorphism (g.-1296T>C, rs9619311). Plasma MMP-9 and TIMP-1 levels were measured by ELISA. GH patients with the GG genotype for the TIMP-1 polymorphism had lower MMP-9 levels and MMP-9/TIMP-1 ratios than those with the TT genotype. PE patients with the TG genotype had higher TIMP-1 levels. The G allele and the GG genotype were associated with PE and responsiveness to antihypertensive therapy in PE, but not in GH. Our results suggest that the TIMP-1 g.-9830T>G polymorphism not only promotes PE but also decreases the responses to antihypertensive therapy.